2019
DOI: 10.1038/s41431-019-0368-7
|View full text |Cite
|
Sign up to set email alerts
|

Continental drift? Do European clinical genetic testing laboratories have a patent problem?

Abstract: Recent US Supreme Court decisions have invalidated patent claims on isolated genomic DNA, and testing methods that applied medical correlations using conventional techniques. As a consequence, US genetic testing laboratories have a relatively low risk of infringing patents on naturally occurring DNA or methods for detecting genomic variants. In Europe, however, such claims remain patentable, and European laboratories risk infringing them. We report the results from a survey that collected data on the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Furthermore, the use of the human pangenome could also lead to further legal issues in the field of intellectual property. For instance, if a gene or genes were to be identified as being responsible for a particular trait, then it might be possible to patent those genes [ 150 , 151 , 152 , 153 ]. This could potentially lead to disagreements over who has the rights to the gene and its uses.…”
Section: Technical Ethical and Legal Considerationsmentioning
confidence: 99%
“…Furthermore, the use of the human pangenome could also lead to further legal issues in the field of intellectual property. For instance, if a gene or genes were to be identified as being responsible for a particular trait, then it might be possible to patent those genes [ 150 , 151 , 152 , 153 ]. This could potentially lead to disagreements over who has the rights to the gene and its uses.…”
Section: Technical Ethical and Legal Considerationsmentioning
confidence: 99%
“…It was alleged in early 2013 that patenting the MERS virus hampered the rapid development of diagnostics, specifically in Saudi Arabia, and that the novelty requirement for patentability may have tempted scientists to delay the publication of data urgently needed to contain the virus and to develop diagnostics 12 . However, a recent comprehensive survey showed that relevant patents do not affect most diagnostic labs in terms of their innovation, product development and provision of diagnostic services, although a nominal increase in the number of affected labs was observed 13 . Moreover, a patent can be enforced only once it is published and granted, which usually takes at least 18 months.…”
Section: The Impact Of the Patent On Researchmentioning
confidence: 99%
“…Erasmus MC argued that a patent was necessary to attract investments in the development of diagnostics, vaccines and drugs 13 . However, the contributions by academic researchers should not be neglected.…”
Section: The Impact Of the Patent On Researchmentioning
confidence: 99%
“…Patenting of naturally occurring genetic sequences is no longer allowed by the United States Patent and Trademark Office, but it is still allowed in Europe (Cole 2015 ). Whether patenting genomic sequences has a positive or negative impact on healthcare innovation remains under debate (Liddicoat et al 2019 ). Central governance may also be needed to contain data positionality to the sphere of research and innovation.…”
Section: Organizing Responsible Innovation In View Of Data Positionalmentioning
confidence: 99%